(untitled) (Texas Journal of Engineering and Technology, 2025)
The operating conditions of modern industrial vehicles are determined by the increasing depth of mining operations. This trend results in the predominant use of vehicles (over 60%) as assembly units, concentrating vehicle traffic in the working area of deep quarries with their limited space of the Muruntau deep quarry is characterized by a high concentration of traffic, heterogeneity of the transported rock mass, and instability of key parameters. During a shift, 10-15 working faces and 5-10 transfer points are in operation, forming over 100 routes with an average length of 3.73 km